Intralimb gait coordination of individuals with stroke using vector coding - Celestino, Melissa L.; van Emmerik, Richard; Barela, Jose A. [UNESP]; Gama, Gabriela L.; Barela, Ana M. F. (Elsevier B.V., 2019)
Individuals with stroke often present functional impairment and gait alteration. Among different aspects, intralimb coordination of these individuals is one of the key points that should be considered before implementing any gait intervention protocol. The purpose of this study was to investigate the effects of stroke on intralimb gait coordination of the lower limbs using a vector coding technique. Twenty-five individuals with stroke and 18 non-disabled individuals (control), between 46 and 71 years old, participated in this study. A computerized analysis system registered data from reflective markers placed on specific body landmarks to define thigh, shank, and foot of both body sides, as participants walked at self-selected comfortable speed. Coordination modes, such as in-phase, anti-phase, proximal-segment-phase, and distal-segment-phase, and variability of thigh-shank, and shank-foot were analyzed for the paretic, non-paretic and control limbs during the stance and swing periods, and the entire gait cycle using the vector coding technique. During the stance period, individuals with stroke presented higher frequency of thigh-phase and lower frequency of shank-phase for the thigh-shank coupling and higher frequency of shank-phase for the shank-foot coupling compared to non-disabled controls, indicating that the proximal segment of each pair leads the movement. During the swing period, the paretic limb presented higher frequency for in-phase than non-paretic and control limbs for the thigh-shank coupling. Adaptations in the non-paretic limb were observed in the swing period, with higher frequency than paretic and control limbs in the thigh-phase for the thigh-shank coupling, and higher frequency than the paretic limb in the foot-phase for the shank-foot coupling. No differences in coordination variability were found between paretic, non-paretic, and control limbs. The vector coding technique constitutes a useful tool for identifying gait alterations in intralimb coordination of individuals with stroke. Our coordination results demonstrate a shift from distal to more proximal control during the stance phase in both legs for the individuals with stroke and an inability to decouple segment coordination during the swing phase in the paretic limb. The results indicate that it is more suitable to consider the stance and swing periods separately instead of considering the entire gait cycle to investigate intralimb gait coordination of individuals with stroke.
Keywords: Locomotor coordination; Coordination variability; Vector coding technique